How much, how often, how well? Adherence to a neuromuscular training warm-up injury prevention program in youth basketball - Owoeye, O. B. A.; Emery, C. A.; Befus, K.; Palacios-Derflingher, L.; Pasanen, K. (Journal of Sports Sciences, 2020)
Adherence is a key implementation outcome that determines the effectiveness of an intervention. This study, an observational design involving coaches and players from 33 high school basketball teams, evaluated the dimensions of adherence to a basketball-specific neuromuscular training (NMT) warm-up program in youth basketball. Coach adherence (daily report of team adherence) was collected prospectively. Adherence measures: cumulative utilization (proportion of total sessions possible), utilization fidelity (average # of exercises completed per NMT session), utilization frequency (average # of NMT sessions completed per week) were calculated and further evaluated for optimal adherence (=80%, =10.4 exercises/session and =2 sessions/week, respectively) per coach. Additionally, exercise fidelity (proportion of players performing individual exercises correctly) was assessed. Coach (n = 31; 27-59 years) median cumulative utilization was 80%, utilization fidelity was 12 (of a possible 13 exercises per session) and utilization frequency was 2.3 sessions per week. Optimal adherence ranged from 52% to 71% across measures of adherence. Player exercise fidelity was 48%. Time constraint (47%) was the most frequently reported adherence barrier. While coach adherence to the NMT warm-up program was reasonably high across measures of adherence, a considerable proportion of coaches did not attain optimal adherence levels and player exercise fidelity was low.